IMPLEMENTASI STUDENT WELLBEING DI SMP KECAMATAN PAKIS AJI KABUPATEN JEPARA - Munif Hidayati; Nurkolis; Soedjono (STKIP Subang, 2023)
The aim of this research is to find out: (1) Planning for student welfare at Pakis Aji District Middle School, Jepara Regency; (2) Implementation of student welfare at Pakis Aji District Middle School, Jepara Regency; (3) Evaluation of student welfare at Pakis Aji District Middle School, Jepara Regency. Research method, type of qualitative research with a case study approach. The sampling technique used was purposive sampling. Data collection techniques, interviews, observation, documentation, and FGD. Test the validity of the data using triangulation and extension of participation. The data analysis technique uses qualitative descriptions. The research results concluded: (1) Student welfare planning at Pakis Aji District Middle School, Jepara Regency has been well planned according to procedures, implementation instructions and technical instructions, neatly arranged, detailed and equipped with complete documents. Student welfare planning includes vision and mission, goals, strategies, involvement of parties, implementation time and organization of activities which emphasize the formation of students' interpersonal and intrapersonal attitudes at school. Student welfare planning is included in school program documents, intracurricular and extracurricular activity programs, and funding is outlined in the RKAS which is approved by the school principal and recommended by the supervisor and reported to the Jepara District Education, Youth and Sports Office. (2) Implementation of student welfare at Pakis Aji District Middle School, Jepara Regency is carried out in stages starting from identification, coordination with related parties, implementation focuses on interpersonal and intrapersonal aspects which focus on seven indicators starting from the student's physical condition. students' affective (attitude), students' cognitive (knowledge), students' social (social conditions), conducive school environment, assets (what students have), and students' actions; (3) Evaluation of student welfare at Pakis Aji District Middle School, Regency has been carried out well, starting from planning, implementation, data collection, data verification, data processing and data interpretation, preparation of student welfare report activities. The emphasis in evaluating student welfare includes complete administration of activity programs, implementation of activities starting from physical activities (physical condition) of students. students' affective (attitude), students' cognitive (knowledge), students' social (social conditions), conducive school environment, assets (what students have), and students' actions